Edukasi Dan Skrining Diabetes Mellitus Tipe 2 Melalui Pemeriksaan HbA1c Pada Kelompok Lanjut Usia - Robert Kosasih; Daniel Goh; Tosya Putri Alifia (Pusat Riset dan Inovasi Nasional, 2024)
Type 2 diabetes mellitus is a chronic disease characterized by high blood glucose levels due to insulin resistance or inadequate insulin production. In the elderly, diabetes mellitus causes various serious complications such as heart disease, nerve damage, kidney failure and vision problems. Risk factors for diabetes mellitus include family history, obesity, lack of physical activity, a diet high in fat and sugar, and hypertension. This community service activity aims to increase awareness and early detection of type 2 diabetes mellitus through education and HbA1c screening in the elderly. Of the 93 lanjut usiats, 74 were women and 19 were men, with an average age of 74.05 years. The mean HbA1c value was 7.59, with 55.9% in the moderate category and 25.8% in the poor category. Results showed that suboptimal glycemic control was higher in women. This program highlights the need for regular monitoring and appropriate interventions to improve glycemic control and quality of life for older adults through comprehensive education, physical activity and stress management.